A dictionary of drug abuse terms and terminology - Abel, Ernest L. 1943- (Greenwood Press, 1984)
"Words and expressions dealing with drugs of abuse along with some technical terms." Excludes in general terminology relating to alcohol and tobacco. Brief explanatory definitions. Glossary that brings together similar terms. Bibliography.